2017
DOI: 10.1016/j.jenvman.2017.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Single, simultaneous and consecutive biosorption of Cr(VI) and Orange II onto chemically modified masau stones

Abstract: Novel and low cost chemically modified masau stone (CMMS) was investigated for its biosorption of an anionic azo dye, Orange II (OII), and toxic hexavalent chromium (Cr(VI)) from aqueous systems: individually, simultaneously and consecutively. XPS and FTIR analyses indicated the introduction of quaternary-Nitrogen to the CMMS surface after activation with epichlorohydrin (etherifying agent) and diethylenetriamine (crosslinking agent). The effects of pH, contact time and initial concentration (C), and loading o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…5). This stems from the fact that the higher the dose of the adsorbent, the greater the availability of exchangeable sites for Ace molecules [31].…”
Section: Effects Of Dosementioning
confidence: 99%
“…5). This stems from the fact that the higher the dose of the adsorbent, the greater the availability of exchangeable sites for Ace molecules [31].…”
Section: Effects Of Dosementioning
confidence: 99%
“…In a recent study [ 18 ], it was shown that modification of natural Populus tremula fibers with amino ligands led to increased adsorption capacity of acid blue 25 from 22.33 mg/g for unmodified to 48 mg/g for hydrazine fiber and 67 mg/g for ethylenediamine fiber. Masau stones were chemically modified with diethylenetriamine through a cross-linking protocol, and 87.32 mg/g adsorption capacity was reported [ 19 ]. The presence of protonated amino groups at acidic conditions was credited to the biosorption-coupled reduction removal mechanism of Cr(VI).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the dominant adsorption-reduction mechanism, recent studies have reported three mechanisms all taking place simultaneously, ion-exchange, electrostatic attraction, and reduction. 34,36 The ion exchange mechanism was explained on the basis of the presence of CO 3 2À in the interlayer structures of magnetic particles imprinted cellulose-based biocomposites made from hydrotalcite (HT) and hydroxyapatite (Hap). 36 The electrostatic attraction of chromate anions to the adsorbent's surface could be the result of the presence of higher valence cations like Ca 2+ , Mg 2+ and Fe 3+ in the adsorbent 36 as indicated in Fig.…”
Section: Mechanisms Of Chromium Removal (Advancement In Interpretation)mentioning
confidence: 99%
“…The typical study, Masau stones cross-linked with epichlorohydrin (ECH) and graed with diethylenetriamine (DETA) were experimented for the removal of Cr(VI) from aqueous solutions. 34 The adsorption capacity of 87.33 mg g À1 was achieved within 250 min. A complex mechanism of removal involving adsorption of Cr(VI) through electrostatic attraction, hydrogen bonding, and p-p interactions was reported.…”
mentioning
confidence: 96%
See 1 more Smart Citation